Cannabis in combat sports: position statement of the Association of Ringside Physicians - Stellpflug, S. J.; Stolbach, A.; Ghorayeb, J.; Magraken, E.; Twohey, E.; Lapoint, J.; deWeber, K. (The Physician and Sportsmedicine, 2024)
Abstract and ARP Position Statement: Based on the available body of scientific evidence and with the goals of promoting safety of combat sports athletes and striving for the advancement of clean sport, the Association of Ringside Physicians recommends the following regarding cannabis: